Preferential Effects of Cariprazine on Counteracting the Disruption of Social Interaction and Decrease in Extracellular Dopamine Levels Induced by the Dopamine D3 Receptor Agonist, PD-128907 in Rats: Implications for the Treatment of Negative and Depressive Symptoms of Psychiatric Disorders - Kehr, Jan; Wang, Fu-Hua; Ichinose, Fumio; Yoshitake, Shimako; Farkas, Bence; Kiss, Béla; Adham, Nika (Frontiers in Psychiatry, 2022)
The negative and cognitive symptoms of schizophrenia and related disorders may be due to reduced dopaminergic tone in cortical brain areas. Alteration in the function of dopamine (DA) D3 receptors may play a role in this cortical hypofunctionality and underlie the deficits in social behaviors and cognitive functions in schizophrenia. Cariprazine is a potent DA D3-preferring D3/D2 receptor partial agonist that is approved for the treatment of schizophrenia and bipolar disorder. The objective of the study was to compare the abilities of cariprazine, aripiprazole (another DA receptor partial agonist with more D2 receptor preference), and ABT-925 (a selective DA D3 antagonist) to counteract the social deficit and neurochemical alterations induced by the D3 receptor-preferring agonist (+)-PD 128907 (PD) in rats. Administration of PD (0.16 mg/kg; s.c.) induced a marked (-72%) but short-lasting disruption of the defensive social aggregation behavior (huddling) in the first 10-minute period. Cariprazine at all doses (0.1, 0.3, 1 mg/kg; p.o.) almost completely abolished the PD-induced disruption of huddling. Likewise, ABT-925 (3 mg/kg; p.o.) and to a lesser extent aripiprazole (20 mg/kg; p.o.) were effective in blocking the PD-induced disruption of huddling. As measured by microdialysis, the highest dose of cariprazine prevented a PD-induced decrease in DA levels (40-80 minutes post PD dose) in the medial prefrontal cortex (mPFC), whereas aripiprazole did not have a significant effect. ABT-925 significantly counteracted the effect of PD at 80 minutes post-dose. In the nucleus accumbens (nAcc) shell, the highest dose of cariprazine, as well as ABT-925 and aripiprazole, significantly reversed the PD-induced decrease in DA levels. Taken together, these data provide behavioral and in vivo neurochemical evidence for the preferential DA D3 receptor action of cariprazine in the rat. This property of cariprazine may offer therapeutic benefits against the cognitive deficits and negative/depressive symptoms of schizophrenia and related disorders.